Selected poetry and prose - Matraini, Chiara, 1515-1604? (Other voice in early modern Europe., 2007)
Chiara Matraini (1515-1604?) was a member of the great flowering of poetic imitators and innovators in the Italian literary heritage begun by Petrarch, cultivated later by the lyric poet Pietro Bembo, and supplanted by the epic poet Torquato Tasso. Though without formal training, Matraini excelled in a number of literary genres popular at the time--poetry, religious meditation, discourse, and dialogue. In her midlife, she published a collection of erotic love poetry, but later in life her work shifted toward a search for spiritual salvation. Near the end of her life, she published a new poetry.